Methadone toxicity: comparing tablet and syrup formulations during a decade in an academic poison center of Iran. (September 2013) - Shadnia, S.; Rahimi, M.; Hassanian-Moghaddam, H.; Soltaninejad, K.; Noroozi, A.
Abstract Context. Due to an increase in the number of methadone maintenance clinics in the past decade in Iran, acute methadone overdose has become one of the common poisonings in our society. Objective. To compare the characteristics of methadone poisoning between syrup and tablet formulation as well as to discuss the relative advantages and disadvantages of poisoning from the perspective of toxicity. Material and methods. In a retrospective cross-sectional study from 2000 to 2010, sampled data of all hospitalized methadone-overdosed patients were collected through chart review of hospital records. Concurrently, the total number of methadone sales was gathered. Results. A total of 1426 patients with methadone poisoning had been hospitalized, including 1072 cases who consumed syrup or tablet solely. Mean ± SD milligram ingested dose of syrup and tablet were 153 ± 339 and 88 ± 274, respectively (p < 0.001). The mean time elapsed since ingestion was 9 ± 9 and 7 ± 7 h, respectively. Most of the accidental poisoning cases occurred as a result of syrup formulation, particularly by children under 12 years old after being mistaken for cough mixture or water. Conversely, exposure to methadone tablets was more common in patients with suicidal intent. There was no statistically significant difference between the rates of intubation and death between the two groups. Discussion. Higher doses of methadone in the syrup form appear to exert a similar severity of poisoning and outcomes compared to lesser doses of that in the tablet form. Similarities in outcomes, despite differences in exposure history, may reflect relatively prompt transfer to hospital and adequate provision of clinical care, including supportive care and naloxone. Conclusion. In order to reduce the rate of poisoning, we recommend the use of child-resistant containers for dispensing syrup, reduction in methadone concentration, adding a coloring agent, special flavor, and education of patients on the safe storage of methadone in their home in order to reduce the occurrence of accidental poisonings.